Towards a green enantiomeric esterification of R/S-ketoprofen: a theoretical and experimental investigation - Toledo, Victoria (2015)
Methanol, ethanol, 1- and 2-propanol were used as reactants and solvents in the esterification of R/S-ketoprofen catalyzed with Novozym® 435. The interaction of the alcohols with Novozym® 435 was studied at a molecular level through various spectroscopic techniques and molecular modeling. The results evidenced the dissolution of the polymeric support, loss of active protein, strong adsorption of the alcohols, modification of the secondary structure of the protein and smoothing of the inner structure of the biocatalyst's beads upon extended contact with the alcohols. Nevertheless, none of those drawbacks influences the specific activity and enantiomeric excess toward S(+)-enantiomer that remain unaltered upon extended contact with ethanol, 1- and 2-propanol as acyl acceptors. However, theoretical calculations demonstrated that methanol introduces steric and electronic hindrance within the step of the coordination of the R/S-ketoprofen with the catalytic triad.